A CROSS-CONTINENTAL EXAMINATION AND COMPARISON OF DESCRIPTIVE CRITERIA IN MARKETING JOURNALS â€“ AMJ, EJM AND JM - Svensson, GÃ¶ran; Wood, Greg (Revista de Negócios, 2008)
The objective is to perform a cross-continental examination and comparison of non-traditional descriptive criteria in a selection of leading academic journals in marketing. The sample of journals is restricted to the examination and comparison of three academic journals in marketing. The journal sample consists of the Australasian Marketing Journal (AMJ), the European Journal of Marketing (EJM) and the Journal of Marketing (JM). Empirical research manuscripts dominate in the selected marketing journals. In addition, in the selected journals regular issues dominate in favour of special issues. The descriptive criteria examined and compared in AMJ, EJM and JM are based upon the content analysis of 811 manuscripts published during a six-year period, namely 2000-2005. Manuscripts of types other than empirical research, such as general reviews, literature reviews, conceptual papers, commentaries and book reviews are less likely to get published. Special issues or special sections are less frequent in these journals. This may lead to the situation that specialized journals in sub-areas of marketing may provide better and more comprehensive leading edge coverage and knowledge. The insights provided are in particular valuable for those scholars that do not usually get involved in academic publishing and consequently have a limited understanding and experience of the publication arena of manuscripts in leading academic journals. These insights also will be informative for more experienced academic publishers as they highlight certain characteristics of these journals that enlighten one as to the journals that one should target for publication and the difficulty, just on a numbers basis alone, of getting published in one of these three journals. The principal contribution of this research is the examination and comparison of descriptive criteria in AMJ, EJM and JM â€“ a cross-continental sample of journals and criteria that have not been explored or reported previously in literature. Key words: Marketing. Journals. Descriptive. Criteria. Examination. Comparison. Cross-continental.